Interaksi Sosial di Kalangan Peserta Didik Pada Saat Pembelajaran Online - Rian Rifki Eliandy; En Riskinta Tumanggor; Etti Aini Hasibuan; Toni Nasution (FKIP, Universitas Palangka Raya, 2022)
This article was made with the title Social Interaction Among Students During Online Learning with the aim of being able to inform the wider community how important social interaction among students during online learning is both in terms of education and in terms of family. The method used is descriptive qualitative by using various supporting sources so that it can be seen that in terms of education students become lazy, have difficulty understanding the material, do not continue school, some work or even get married while online learning is applied and in terms of family, children and parents will be able to understand each other because with the implementation of online learning, children and parents have a lot of time to be together so that social interaction or communication occurs more often and better